Respuesta :

Answer:

RS = 11

Step-by-step explanation:

RS + ST = ST

2x-9 + x+2 = 23

Combine like terms

3x -7 =23

Add 7 to each side

3x-7+7 =23+7

3x= 30

Divide by 3

3x/3 = 30/3

x = 10

RS = 2x-9

    = 2(10) -9

       20-9

       11

Answer: 11

Step-by-step explanation:

Since we know RT we can add RS and ST to equal RT.

[tex](2x-9)+(x+2)=23\\[/tex]

The parenthesizes are not necessary, but they help understand the parts of the equation.

We can remove the parenthesizes and then combine like terms.

[tex]3x-7=23\\[/tex]

Now add 7 to both sides to isolate the 3x.

[tex]3x=30\\[/tex]

Now divide by 3 to solve for x.

[tex]x = 10\\[/tex]

Now that we have solved for x we need to plug it back into the RS expression to solve for that length.

[tex]2(10)-9=RS\\[/tex]

Now solve.

RS = 11

ACCESS MORE